2018
DOI: 10.1111/ans.14437
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue balancing in total knee arthroplasty using sensor‐guided assessment: is there a learning curve?

Abstract: This study suggests that there is a learning curve with the use of sensor-guided assessment in TKA in achieving knee balance; however, the differences noted between initial and final groups were small and may not be of clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…For both TKA and UKA, RAS has shown no learning curve with the implant positioning but a significant learning curve with the workflow and instrumentation [3,4,12]. Surgical time flattens out effect after 5-10 cases and, in most studies, reaches a steady value after 8 cases in image-based RAS for UKA and TKA [4,6,11,17,18,20,22]. RAS offers a good opportunity for low-volume arthroplasty surgeons to achieve high levels of implant position accuracy in TKA and UKA [10].…”
Section: Introductionmentioning
confidence: 99%
“…For both TKA and UKA, RAS has shown no learning curve with the implant positioning but a significant learning curve with the workflow and instrumentation [3,4,12]. Surgical time flattens out effect after 5-10 cases and, in most studies, reaches a steady value after 8 cases in image-based RAS for UKA and TKA [4,6,11,17,18,20,22]. RAS offers a good opportunity for low-volume arthroplasty surgeons to achieve high levels of implant position accuracy in TKA and UKA [10].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining three had used them intermittently in previous TKAs, but then intensively for 15 to 30 cases prior to the start of the study, experience which has been shown to mitigate any learning curve. 21 A pragmatic approach was used for the inclusion of patients: all those aged between 20 and 85 years who were scheduled for primary TKA to treat primary osteoarthritis, inflammatory arthritis, or post-traumatic arthritis were eligible. Those undergoing unilateral or bilateral procedures, those with extraarticular deformity from previous fracture or osteotomy, and those with severe stiffness were also included, but those who required constrained prostheses due to significant ligament deficiencies, and those undergoing TKA for acute fracture or tumour, were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In a single-surgeon experience, Lakra et al retrospectively quantified, using a CUSUM (cumulative sum control chart) analysis, their learning curve after performing 41 sensing technology-augmented total knee arthroplasties, showing an increase in the mean operative time of 11 minutes 41 . In a consecutive series of 90 total knee arthroplasties, Gharaibeh et al hypothesized that a surgeon's development of fine-tuning skills to obtain a well-balanced knee could be quantitatively demonstrated to occur within the first 30 cases 42 .…”
Section: Limitationsmentioning
confidence: 99%